Occurrence and Behavior of Residual Pharmaceuticals in the Nakdong River Basin - Chang-Dong Seo; Hoon-Sik Yoom; Mi-Jeong Song; Kyung-A Kim; Si-Young Kim; Heejong Son (대한환경공학회지, 2020)
Objectives This study was conducted to evaluate the detection characteristics of Nakdong River basin (wastewater treatment plant (WWTP) effluents, tributaries and main streams) by selecting 18 kinds of pharmaceuticals which were detected frequently. It was intended to be used as basic data for advanced treatment of WWTP and securing safe water source. Methods The selected 18 pharmaceuticals investigated in this study were acetaminophen, atenolol, carbamazepine, caffeine, diclofenac, iopromide, lincomycin, metoprolol, primidone, propranolol, sulfachloropyridazine, sulfamethazine, sulfamethoxazole, tetracycline, trimethoprim, chlorotetracycline, oxytetracycline and sulfathiazole. The residual pharmaceuticals was analyzed LC-MS/MS equipped with on-line solid phase extraction (SPE) system and the limit of quantifications (LOQ) of 18 residual pharmaceuticals were 1~5 ng/L. Sampling points were 27 from the upstream to the downstream, including mainstream, tributary, and WWTP effluents. Sampling was conducted four times in Feb., Jun., Aug. and Nov. 2018. Results and Discussion The most frequently detected residual pharmaceutical in all WWTP effluents, tributaries and mainstream sites was caffeine, followed by carbamazepine, lincomycin, sulfamethoxazole and iopromide. In addition, iopromide was detected as the highest mean concentration of 44.9~985.4 ng/L followed by caffeine (63.2~337.1 ng/L) and carbamazepine (13.8~145.0 ng/L), sulfamethoxazole (12.3~114.8 ng/L) and diclofenac (3.1~144.1 ng/L). In particular, the proportion ratio of caffeine gradually decreased as going to the downstream, whereas iopromide gradually increased. However, the concentrations of caffeine in the sampling sites of the downstream were higher than those of the upstream sites. The total concentrations of detected residual pharmaceuticals gradually increased from the upstream to the middle stream, showed the highest detected concentration at the Goryeong area in the middle stream of the Nakdong River, and then gradually decreased due to the dilution effect. Residual pharmaceuticals in the Nakdong River basin, which could not be completely removed from the WWTPs, entered into the water system and contaminated source water of the downstream. This process is a typical contaminant pattern of the source water by the emerging micropollutants. Conclusions The most frequently detected residual pharmaceutical in all WWTP effluents, tributaries and mainstream sites was caffeine, followed by carbamazepine, lincomycin, sulfamethoxazole and iopromide. In addition, iopromide was detected as 44.9~985.4 ng/L, showing the highest mean concentration at the sampling points, and caffeine (63.2~337.1 ng/L) and carbamazepine (13.8~145.0 ng/L), sulfamethoxazole (12.3~114.8 ng/L) and diclofenac (3.1~144.1 ng/L) in order. The total concentrations of detected residual pharmaceuticals gradually increased from the upstream to the middle stream, showed the highest concentration at the Goryeong area in the middle stream of the Nakdong River basin, and then gradually decreased due to the dilution effect.